2022
DOI: 10.21037/tcr-22-1162
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab in the treatment of tislelizumab-induced steroid-refractory immune checkpoint inhibitor-related pneumonia: case report and literature review

Abstract: Background: Infliximab has been recommended by the American Society of Clinical Oncology (ASCO) guidelines for the treatment of steroid-refractory immune checkpoint inhibitor-related pneumonia (CIP), but clinical evidence remains insufficient. In order to improve the level of diagnosis and treatment and rational use of infliximab in the treatment of CIP, a successful case is reported and the relevant literature is reviewed.Case Description: We report a 67-year-old male patient with small cell lung cancer (SCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This represents the first documented case of refractory immune-related thrombocytopenia and anemia occurring simultaneously, notable for its occurrence in SCLC, while previous cases were observed in patients with NSCLC and melanoma [53,54]. Chen et al reported an unusual increase in hepatitis B surface antibody (HBs Ab) in a 62-year-old patient with brain metastasis who was previously HBsAg-negative [32]. This patient was asymptomatic, and it was the first report of a continuous rise in HBs Ab levels following PD-L1 therapy.…”
Section: Immune Checkpoint Inhibitor As Monotherapymentioning
confidence: 77%
“…This represents the first documented case of refractory immune-related thrombocytopenia and anemia occurring simultaneously, notable for its occurrence in SCLC, while previous cases were observed in patients with NSCLC and melanoma [53,54]. Chen et al reported an unusual increase in hepatitis B surface antibody (HBs Ab) in a 62-year-old patient with brain metastasis who was previously HBsAg-negative [32]. This patient was asymptomatic, and it was the first report of a continuous rise in HBs Ab levels following PD-L1 therapy.…”
Section: Immune Checkpoint Inhibitor As Monotherapymentioning
confidence: 77%
“…Elevated IL-1β at baseline and early in anti-PD-1 therapy (1-6 weeks after anti-PD-1 therapy) is predictive of irAEs ( 70 ). A case report demonstrated that the levels of IL-1β were significantly elevated in the serum of CIP patients (21.9 pg/ml) ( 82 ). Suresh et al ( 50 ) observed that the number of monocytes expressing IL-1β in the BALF increased noticeably, while soluble IL-1β levels decreased during the development of CIP.…”
Section: Pathogenesis Of Cipmentioning
confidence: 99%